TREATMENT OF ADULT INTUSSUSCEPTION WITH NON-OPERATIVE MANAGEMENT: A CASE REPORT - Rahman, Shahrul; Anas, Muhammad Al (Universitas Muhammadiyah Sumatera Utara, 2021)
Intussusceptions, defined as insertion of proximal part of intestine into distal one, it is the second most common acute abdomen pathology after appendicitis. Acute intussusception is one of the common causes of acute intestinal obstruction in children, but on seldom occasions associated with leading points to the intussusceptions. The symptoms are the result of intussusception, like intestinal obstruction, volvulus due to subserosa lipoma and hemorrhage due to ulcerations of the overlying mucosa caused by direct pressure from the lipoma or the intussusception itself. Intussusception in adults is very rare. Most intussusception cases must be treated surgically. In patients who present with a vague history and constellation of abdominal symptoms pointing towards obstruction and are found to have a short segment intussusception, it is a valid option to apply a conservative approach with caution. Based on the available literature, CT scan evaluation seems to have both diagnostic and prognostic value, as it provides enough evidence with regards to signs indicating the need for surgery. Herewith, we describe a rare case of intussusception in Indonesian adult which was successfully treated non-surgically